Factors Affecting Individual Taxpayer Compliance on Tax Return After Using E-Filing - Hendro Lukman; Fanny Andriani Setiawan; Juni Simina (International Journal of Application on Economics and Business, 2023)
Tax Return for Individual Taxpayers in Indonesia using e-filing has started since the 2015 tax year which was reported in 2016. The increase in using e-filing showed an increase. However, the increase in Tax Return Reporting for Individual Taxpayers has not shown their compliance in carrying out their obligations, it is seen that reporting is still low compared to those registered, around 56%. This study analyzes the influence of Taxpayer Behavior and Ethics on Taxpayer Compliance. This study is a quantitative study with primary data that obtained through questionnaires, and those were analyzed using the multiple regression method which was processed using PLS Software Version 3. The research subjects were Individual Taxpayers who were registered at the Tax Office in Jakarta and surrounding areas, and had used efiling. The collection of samples during March 2022, collected 55 data from respondents who meet the requirements. The result showed that Taxpayer Ethics had an effect on taxpayer compliance, but Taxpayer Behavior showed the opposite result. The factor with the lowest coefficient of Taxpayer behavior is the perceived lack of tax benefits. Thus, the implications of this study are the Directorate General of Taxes, in this case Section Counseling, Services, and Public Relations (P2Humas) may create counseling programs that explain and provide concrete examples of the benefits of paying taxes, not just only persuading taxpayers to report.